Artistic interpretation in the film ’The Count of Monte Cristo’ (a topical message for contemporary society) - Orban, Karol (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2021)
Alexander Dumas’s legendary novel The Count of Monte Cristo has been in the last decade of the twentieth century successfully adapted several times on television with slight changes to the context of the original story (different ending) in order to preserve the dynamics and gripping nature of the media product. The film builds on high stylization, its overall character is enhanced by powerfully acted scenes and excellent photography both indoors and outdoors. The film clearly communicates frame of mind of the characters, and their behaviour mostly corresponds with the novel; i.e. the context of the original has been maintained. The article describes technical, psychological and especially moral value aspects in the form of defining the key message for current social issues.